Students’ Learning Style and Their Perception in Speaking Subjects at English Department of Universitas Muhammadiyah Parepare - Zulfrida Marzuki (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2020)
This research was conducted to obtain the learning style that commonly apllied in Speaking Subjects by students of English Department of Universitas Muhammadiyah Parepare. This research also conducted to obtain the importance of knowing learning styles that apllied in Speaking Subjects of English Department of Universitas Muhammadiyah Parepare based on students’ perception. This research used Qualitative Descriptive by design conducted with students. The population of this research is English Department of Universitas Muhammadiyah Parepare. The respondents of this research consist of six respondents. In addition, the researcher conducted interview and questionnaire to obtained the data. The result of this research showed that the kind of learning style that commonly apllied in speaking subjects by students are kinesthetic and auditory based on the result of interview and questionnaire. Learning style kinesthetic was the highest score based on the result of questionnaire, the second was auditory, the third was read/write, and the lowest score was visual. Besides, the result of this research also showed that students’ perception toward the importance of knowing learning style especially in speaking subjects stated that learning style is one of the important things to know and understand by students because it plays an important role in learning process for students themselves.